Leukopenia as a Prognostic Factor in Severe Community-Acquired Pneumonia with Sepsis: A Case Report - Irawan, Dandy; Irvan Medison; Dewi Wahyu Fitrina; Dessy Mizarti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Community-acquired pneumonia (CAP) is a major cause of sepsis, and severe CAP with sepsis is associated with significant morbidity and mortality. Leukopenia, a decrease in white blood cell count, has been identified as a potential prognostic factor in sepsis, suggesting a poorer outcome. This case report aims to evaluate the role of leukopenia in predicting the clinical course and outcome of a patient with severe CAP and sepsis. Case presentation: A 73-year-old male presented with complaints of shortness of breath, cough, fever, and altered mental status. He was diagnosed with severe CAP with sepsis and sepsis-associated encephalopathy (SAE). Laboratory investigations revealed leukopenia. The patient's clinical condition improved over 10 days of treatment, coinciding with an improvement in his white blood cell count. Conclusion: This case report highlights the potential prognostic value of leukopenia in patients with severe CAP and sepsis. The patient's clinical improvement paralleled the recovery of his white blood cell count, suggesting that leukopenia may serve as a marker of disease severity and treatment response. Further studies are needed to validate these findings and establish the role of leukopenia in the management of severe CAP with sepsis.